MODEL PEMBELAJARAN ENTREPRENEURSHIP BERBASIS CREATIVEPRENEURSHIP PADA PROGRAM STUDI MAGISTER MANAJEMEN - Eddy Supriyatna; Indra Widjaja; Maria Florencia; Jethro Alva; Jessica Sarkiwan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Entrepreneurs are creators, innovators, and leaders. This means that entrepreneurship is not only the study of business, economics, and management. In fact, in the 21st Century, entrepreneurship has the main focus on the study of New Venture Creation. The word